Development and clinical evaluation of laser-sintered ankle foot orthoses. (2nd January 2018) - Deckers, Jan Patrick; Vermandel, Miguel; Geldhof, Jeroen; Vasiliauskaite, Egle; Forward, Malcolm; Plasschaert, Frank
ABSTRACT: Ankle foot orthoses (AFOs) are traditionally manufactured using vacuum thermoforming as shaping technology. Additive manufacturing has the potential to disruptively change the way these orthopaedic devices are produced. In this study, AFOs are developed which are virtually designed and produced with laser sintering as shaping technology. The mechanical and clinical performances of these laser-sintered AFOs are compared with traditionally manufactured AFO by asking seven patients (both children and adults) to walk with each type of AFO.